A Systematic Literature Review of Educational Management Strategies To Enhance Learning Quality - A. Hadijah Sulfiyani A; Andi Rizka Ekaputri (Kilau Publishing, 2026)
This study aims to identify, classify, and evaluate educational management strategies in improving learning quality through a systematic literature review approach. The data were collected from the Scopus database within the 2015–2025 publication period. The initial search identified 145 documents, which were then filtered based on inclusion and exclusion criteria related to relevance, document type, language, and subject area. After the screening process using Rayyan through title, abstract, and full-text assessment, 9 articles were selected for final analysis. The analysis was conducted using a combination of bibliometric visualization through VOSviewer and table-based thematic synthesis. The results reveal four main categories of strategies, namely leadership-based strategies, collaborative strategies, capacity-building strategies, and system and innovation strategies. Leadership plays a central role as the main driver of learning quality improvement; however, its effectiveness depends on integration with collaboration, capacity development, and systemic support. Overlay visualization also indicates a shift in research trends from leadership-centered approaches toward more integrative and learning outcome-oriented strategies. In addition, the study identifies several research gaps, particularly the limited integration across management strategies and the lack of methodological diversity in previous studies. This study provides a comprehensive synthesis of educational management strategies and highlights the importance of adaptive and integrative approaches to improving learning quality.